Maturity Evaluation of Information Technology Governance in PT DEF Using Cobit 5 Framework - Putri, Mayang Anglingsari; Aknuranda, Ismiarta; Mahmudy, Wayan Firdaus (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
Information technology governance is used to guide and control an organization in achieving the goals that had been planned in advance. PT DEF is a company which utilises information technology to support its business processes. Nevertheless, it indeed requires an IT governance that can be beneficial as a reference for IT activities in order to run properly. This research intends to conduct an audit of information technology governance based on the COBIT 5 framework domain, which is DSS (Deliver, Service, and Support) domain in the process of DSS03 (Manage Problems). According to the research results, the values that have been obtained from the process of DSS03 capability level was 64.66%, that is regarded as Partially Achieved. Capability level will be used as a reference in seeking gap contained in the domain of DSS03 process. Furthermore, these would be able to make recommendations aimed at increasing the value of the expected maturity. This research contributes to the evaluation results and recommendations to improve the capability level on the DSS03 domain, hence PT DEF can upgrade its IT governance by using DSS03 process.